Science Education: Issues, Approaches and Challenges - Shairose Irfan Jessani (Journal of Education and Educational Development, 2020)
In today’s global education system, science education is much morethan fact-based knowledge. Science education becomes meaninglessand incomprehensible for learners, if the learners are unable to relateit with their lives. It is thus recommended that Pakistan, like manyother countries worldwide should adopt Science Technology Society(STS) approach for delivery of science education. The purpose of theSTS approach lies in developing scientifically literate citizens who canmake conscious decisions about the socio-scientific issues that impacttheir lives. The challenges in adopting this approach for Pakistan lie infour areas that will completely need to be revamped according to STSapproach. These areas include: the examination system; science textbooks;science teacher education programs; and available resourcesand school facilities.
Keywords: hands on learning; Pakistan’s national science curriculum; science education; Science Technology Society (STS) approach